URGENSI PERPUSTAKAAN MASJID DALAM MENCERDASKAN UMAT ISLAM - Muhammad Yusuf; Muhammad Nur Effendi; Fitriani Fitriani (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2023)
The Mosque not only a facility for performing Sholah but also it can becomes a social institution that has many roles for building education, economic and social politic. The Mosque has many function, one of them, as an institution of education. As an institution of education, the mosque can be separated from the exist of the library. The mosque library is one of the kind of special library has function to serve the needs of intellectual people around it. By the presence of library, The mosque has function as a center of education because by the library mosque congregation and the moslem society can learn whatever resulted by the former people and also can follow the developmen information and knowledge positively.